SNP marker integration and QTL analysis of 12 agronomic and morphological traits in F8 RILs of pepper (Capsicum annuum L.) - Lu, Fu-Hao; Kwon, Soon-Wook; Yoon, Min-Young; Kim, Ki-Taek; Cho, Myeong-Cheoul; Yoon, Moo-Kyung; Park, Yong-Jin (Molecules and cells, 2012)
Red pepper, Capsicum annuum L., has been attracting geneticists’ and breeders’ attention as one of the important agronomic crops. This study was to integrate 41 SNP markers newly developed from comparative transcriptomes into a previous linkage map, and map 12 agronomic and morphological traits into the integrated map. A total of 39 markers found precise position and were assigned to 13 linkage groups (LGs) as well as the unassigned LGe, leading to total 458 molecular markers present in this genetic map. Linkage mapping was supported by the physical mapping to tomato and potato genomes using BLAST retrieving, revealing at least two-thirds of the markers mapped to the corresponding LGs. A sum of 23 quantitative trait loci from 11 traits was detected using the composite interval mapping algorithm. A consistent interval between a035_1 and a170_1 on LG5 was detected as a main-effect locus among the resistance QTLs to Phytophthora capsici at high-, intermediate- and low-level tests, and interactions between the QTLs for high-level resistance test were found. Considering the epistatic effect, those QTLs could explain up to 98.25% of the phenotype variations of resistance. Moreover, 17 QTLs for another eight traits were found to locate on LG3, 4, and 12 mostly with varying phenotypic contribution. Furthermore, the locus for corolla color was mapped to LG10 as a marker. The integrated map and the QTLs identified would be helpful for current genetics research and crop breeding, especially in the Solanaceae family.